Tribune – Vingt ans de dérive autoritaire de la démocratie en Italie (2001-2021) - Salvatore Palidda (Laboratoire Italien)
Brutalities and tortures by the police forces during the G8 in Genoa is part of an authoritarian drift of democracy in Italy. Since 2001, various crimes and offences, and even homicides by police officers, particularly in prisons, have been repeated at an unprecedented rate over the previous twenty years (1980-2000). This is the result of the guarantee of impunity that the public authorities, and politicians of the right and ex-left alike, have always granted to these officers. Meanwhile, Italian governments, right and ex-left, have continued to extend new privileges and financial resources to the Italian military-police lobby. Furthermore, the implementation of migrations management, according to the logic of “kill and let die”, relegate undocumented migrants, but also many holders of residence permits and certain Italians to precarious jobs or undeclared work in shadow economies.